Chemical composition and digestion of shurbs browsed by white-tailed deer (odocoileus virginianus texanus) - Alvarado, María del Socorro; González Rodríguez, Humberto; Ramírez Lozano, Roque Gonzalo; Cantú Silva, Israel; Gómez Meza, Marco Vinicio; Cotera Correa, Mauricio; Jurado Ybarra, Enrique; Domínguez Gómez, Tilo Gustavo (Medwell, 2012)
The aim of the study was to determine, seasonally, the nutritional value of the native shrubs: Acacia amentacea, Castela erecta, Celtis pallida, Croton cortesianus, Forestiera angustifolia, Karwinskia humboldtiana, Lantana macropoda, Leucophyllum frutescens, Prosopis laevigata, Syderoxylon celastrinum and Zanthoxylum fagara. Leave samples were collected seasonally during 2 years from Summer 2004 to Spring 2006 in three county sites: China, Linares and Los Ramones in the state Nuevo Leon, Mexico and evaluated for the content of their Crude Protein (CP), Neutral Detergent Fiber (NDF) and Acid Detergent Lignin (ADL). Dry Matter Digestibility (DMD) was also estimated. The CP content (range of total means = 13-22% dry matter) in most plants significantly varied among sites and seasons and between years. The same pattern occurred for NDF (40-55), ADL (8-22) and DMD (48-73). Celtis pallida had the highest nutritional value. However, due to their high CP and DMD and low NDF and ADL all studied plants in all sites, most seasons and years may be considered as good food sources for white-tailed deer.